Oral steroids enhance epithelial repair in nasal polyposis via upregulation of the AP-1 gene network. Issue 4 (21st January 2009) - Li, C W; Cheung, W; Lin, Z B; Li, T Y; Lim, J T; Wang, D Y
Abstract : Background: Chronic mucosal inflammation, epithelial damage and aberrant tissue remodelling are common features in nasal polyposis (NP). A study was undertaken to characterise the gene expression profile in NP tissues and to explore the molecular mechanisms underlying the ameliorative effects of glucocorticosteroids (GCs) in NP. Methods: Two sets of NP biopsies (before and after GC treatment) were taken from 10 patients with untreated (GC-naïve) bilateral NP. Biopsy specimens of inferior turbinate from 6 patients who underwent surgery for nasal septal deviation served as nasal mucosal controls. DNA microarrays containing 38 500 genes were used to characterise the global gene expression profile. Functional network analysis was applied to identify the key molecular pathways and genes in response to GC treatment (GC-treated). Selected genes were retested by quantitative RT-PCR and immunohistochemistry in the same polyps and control samples. Results: 64 genes were differentially expressed in GC-treated vs GC-naïve NP tissues. The highest scoring network was assembled around activation protein 1 (AP-1), a heterodimer of c-Fos and c-Jun oncoprotein, and five AP-1-related genes (COX-2, IL-6, AREG, HBEGF and EGR1) with tissue repair function. Quantitative PCR confirmed that AP-1 and its related genes were markedly repressed in GC-naïve polyps and were upregulated after GC treatment. Immunohistochemical staining indicated that epithelial restitution in GC-treated polyps was associated with increased expression of c-Jun protein. Conclusions: Oral steroids promote epithelial repair in NP via upregulation of the AP-1 (especially c-Jun) network and its related genes.